STUDY ON THE NEED FOR THE MODERNIZATION OF CUTTING TOOLS - M. WETTERNEK; S. DIMULESCU (Fiabilitate şi Durabilitate)
This study describes the trend of a new flexible work structure that allows researchers to quickly respond to market demands and respond to many challenges.The dominant feature of the current development phase of this field is the modernization, improvement, innovation of technological processes and products or services with the ultimate goal of satisfying customers